(untitled) (Revista de Medicina Clinica, 2025)
Background: Type 2 diabetes is a chronic metabolic disease that affects multiple organs and is closely linked to overweight and obesity. Its treatment includes diet, physical activity, medications, and monitoring, with nutrition being a key pillar for glycemic control. Well-structured plant-based diets have shown benefits in the prevention and management of T2DM, although they require planning to avoid nutritional deficiencies. This review proposes to evaluate the potential of a vegan diet as a therapeutic tool to improve metabolic indicators and reduce cardiovascular risks. Objective: The objective of this systematic review is to analyze the available scientific evidence on the effects of plant-based diets on type 2 diabetes.Methods: This systematic review aims to rigorously analyze the available scientific evidence to assess whether plant-based diets contribute to improving clinical and functional parameters in these disorders, considering their impact on insulin sensitivity, lipid profile, and health. Results: The review was conducted following the methodological guidelines proposed by the PRISMA statement, which allowed for a transparent, thorough, and carefully structured process at each of its stages. Initially, a total of 5,930 records were identified from four scientific databases recognized for their specialization in health and nutrition: PubMed, Web of Science, ScienceDirect, and Google Scholar. Finally, 8 were selected for analysis. Conclusion: Plant-based diets, when the quality of the consumed foods is prioritized, represent an effective and transformative nutritional strategy for the prevention and management of type 2 diabetes.